2010
DOI: 10.1002/da.20619
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic differences in antidepressant response: a prospective multi-site clinical trial

Abstract: Background Although depression is a highly prevalent condition that occurs in all ethnic groups, the influence of ethnicity on treatment response still remains unclear. Methods A prospective 8-week, open-label clinical trial comparing the efficacy and side-effects of citalopram (CIT) with dose escalation (20–60 mg/day) was performed in African-Americans and Caucasians with non-psychotic major depression. The intent-to-treat sample consisted of 301 participants (169 African Americans and 132 Caucasians). Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
27
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(35 citation statements)
references
References 37 publications
5
27
3
Order By: Relevance
“…In contrast, Caucasian participants did not demonstrate this differential benefit from the Sertraline and thus, there were no differences between outcomes for the Caucasians regardless of whether they received the medication or not. The more favorable response to SS plus sertraline among African American participants is in contrast to previous studies that have shown either poorer or equal response to SSRIs antidepressants among African Americans when compared to Caucasians ((Lesser et al, 2007, 2010, 2011). It is possible that genetic or cultural factors were responsible for the more favorable response (Burroughs, Maxey, & Levy, 2002).…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…In contrast, Caucasian participants did not demonstrate this differential benefit from the Sertraline and thus, there were no differences between outcomes for the Caucasians regardless of whether they received the medication or not. The more favorable response to SS plus sertraline among African American participants is in contrast to previous studies that have shown either poorer or equal response to SSRIs antidepressants among African Americans when compared to Caucasians ((Lesser et al, 2007, 2010, 2011). It is possible that genetic or cultural factors were responsible for the more favorable response (Burroughs, Maxey, & Levy, 2002).…”
Section: Discussioncontrasting
confidence: 98%
“…Differential responses have been attributed to genetic characteristics/factors and cultural practices that might influence the metabolism of the medications (Murphy et al, 2013). Other studies, however, found that African Americans had equivalent responses to antidepressants compared to Caucasians (Lesser et al, 2010, 2011) after controlling for comorbid anxiety disorders and social disparities (e.g., education and employment).…”
mentioning
confidence: 90%
“…Two smaller, subsequently published studies showed no racial group differences in treatment outcome (Lesser et al, 2010;Lesser et al, 2011), although one of the studies reported a high dropout rate for African Americans (Lesser et al, 2011) relative to the other racial and ethnic groups. However, our ability to draw broad conclusions from these recent studies is limited, because both studies differ from STAR*D in terms of sample sizes, methodology, and outcome measures.…”
Section: Discussionmentioning
confidence: 96%
“…Although most studies have found that environmental factors such as lower socioeconomic status (SES), greater medical or psychiatric comorbidity, and higher dropout contribute to the poorer outcomes among African Americans (Warden et al, 2007;Warden et al, 2009;Lesser et al, 2010;Lesser et al, 2011), other studies have suggested that additional biological or genetic factors may also play an important role (Strickland et al, 1997;Luo et al, 2006;McMahon et al, 2006;Lesser et al, 2007). However, conclusions from both types of studies have been limited by methods that were unable to separate individual effects among many intercorrelated variables.…”
Section: Introductionmentioning
confidence: 99%
“…24,25 Thus, it might be inferred that the antidepressant effects of massage might be mediated by mechanisms similar to those of more traditional pharmacologic agents. The profile of response in the massage group also argues against (but does not disprove) a nonspecific or placebo effect.…”
Section: Discussionmentioning
confidence: 99%